CSR and Codes of Business Ethics in the USA, Austria (EU) and China and their Enforcement in International Supply Chain Arbitrations - Peter, Adolf (Springer Nature Singapore : Imprint: Springer, 2021)
XVII, 225 p. 6 illus., 5 illus. in color.